Investigations on the Mechanical Properties of Hot-Rolled and Cold-Formed Steels - Suchampa Bagchi (Mathematical Statistician and Engineering Applications, 2021)
In the construction of buildings, numerous steel components, including hot-rolled and cold-formed hollow sections (Q235), Q345 steel (Q345 or Q420), and other components, are utilized. Steel buildings are subjected to higher temperatures in the event of a fire. "Compare the mechanical properties of cold-formed Q235 steels with various degrees of cold working to those of hot-rolled Q235, Q345, and Q420 steels to determine whether the building can be saved, repaired, or repurposed quickly after the fire." After the samples had reached a variety of temperatures, air and water were used as cooling agents. Tensile coupons tests were used to measure stress and strain in post-fire materials. There are elastic moduli, yield strengths, and ultimate strengths. The processes of heating and cooling were also examined. Steel's mechanical properties change significantly at temperatures above 700 degrees Celsius, according to studies. Cyclic heating and cooling had no effect at all, but various cooling methods had a significant impact. Due to improved prediction models that take these parameters into account, it is now possible to conduct research on the impact of various cooling procedures on the post-fire mechanical features of studied hot-rolled and cold-formed steels.